Contemporary literature: the basics - Gupta, Suman, 1966- (London : Routledge, 2012)
''Contemporary Literature' is a familiar phrase and one of the most popular areas of literary study. But it can be a difficult category to pin down and readers don't have the benefit of a large body of critical secondary literature to consult. Contemporary Literature: The Basics equips readers with the necessary tools to take an analytical and systematic approach to contemporary literary texts. Focusing in particular on the contemporariness of the literature, the books covers: Can there ever be a canon of contemporary literature? How does a reader's own place in the contemporary period impact their understanding of contemporary literature? When does a work of contemporary literature stop being contemporary? Which are the key concepts and themes that are most prevalent in contemporary literature? Containing illustrative examples from prose, poetry and drama, and discussing the topics which define our current sense of the contemporary (globalization, new media, post 9-11) this is an ideal starting point for anyone seeking to engage critically with contemporary literature'--
Includes bibliographical references and index.
Keywords: Literature, Modern -- 21st century -- History and criticism; FICTION / General; LITERARY COLLECTIONS / General; LITERARY CRITICISM / General